Grammatical Errors Found in Undergraduate Thesis Abstracts of International Class Students of the Law Faculty of Syiah Kuala University - Khairunnisa Khairunnisa; Saiful Marhaban; Iskandar Abdul Samad (Universitas Syiah Kuala, 2023)
Writing is considered as the most difficult skill to learn in English. Grammatical errors can be committed when producing a writing product, including in writing undergraduate thesis (UT) abstracts. This study aimed at identifying the grammatical errors found in the UT abstracts written by the international class students of law faculty of Syiah Kuala University using the theory proposed by Ho (2005). The method used in this qualitative research was document analysis method. Fifteen (15) UT abstracts published on the digital library of Syiah Kuala University in 2020 and 2021 were collected and analyzed. Based on the analysis, the researchers found 206 grammatical error cases in the abstracts. Errors regarding sentence structure were the most frequently committed type of error (47.57%), especially in the sub-type of incomplete or fragmented sentence (42.85%). It was then followed by errors regarding noun and noun group (21.35%), errors regarding verb and verb group (16.50%), and errors regarding preposition in the last place (14.56%).